PENERAPAN PENDIDIKAN KESEHATAN DENGAN METODE ICARE BERBASIS FLIPCHART TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG IMS DAN HIV-AIDS DI KOTA BOGOR: - - Sri Wahyuni (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Teenagers are assets and the next generation of the nation that must be physically, mentally and spiritually healthy. Teenagers need to get serious attention because adolescents are included in school age and working age, they are very at risk of reproductive health problems, namely premarital sexual behavior, drug abuse and HIV / AIDS (BKKBN, 2011). One learning model that can be applied is the ICARE learning model. The strength of this ICARE method is that the ICARE system includes five key elements of a good learning experience, which can be applied to students. Therefore, the ICARE system is very good to be applied in the learning process at school. This study uses a Posttest Only Control Group Design. The study was conducted in the Bogor City area. Sampling was done by puorposive random sampling conducted on 30 respondents. Variables were measured using a pre-test post-test instrument before and after the intervention was given in the form of health education using ICARE method based on flipchart. Statistical tests using the Wilxoson and Mann Whitney test. The results of this study have increased knowledge and attitudes of adolescents about STIs and HIV-AIDS after educational interventions using ICARE methods based on flipcharts. The results of the Man Whitney test show that differences in knowledge and attitudes before and after education about STI and HIV-AIDS with ICARE method based on flipchart shows the results that knowledge before and after the intervention obtained a p value of 0.030. meaningful because of interventions in the form of flipchart-based ICARE health education, while the positive increase in adolescent attitudes about HIV-AIDS is not caused by interventions in the form of flipchart-based ICARE health education